The Effect of a Mobile Computer-Supported Collaborative Learning Model Using Phenomenon-Based Learning to Enhance Pre-Cadet Students' Scientific Competencies - Kedtip, Chosita; Koraneekij, Prakob (ECT Education and Communication Technology Journal, 2024)
The purpose of this research was to study the impact of a mobile computer-supported collaborative learning model using phenomenon-based learning aimed at enhancing pre-cadet students' scientific competencies. The sample consisted of 33 pre-cadet students selected through simple random sampling by the lottery method. The research instruments included a learning model and scientific competency assessments. The experiment period lasted 5 weeks. Data were analyzed using mean, standard deviation, and One-way ANOVA with repeated measures. The results showed that the scientific competencies of pre-cadet students differed significantly at the .05 level between the 1st, 3rd, and 5th assessments.